2002
DOI: 10.1051/0004-6361:20020221
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dust on the inverse Compton emission from jets in Active Galactic Nuclei

Abstract: Abstract. The recently observed high energy γ-ray emission from more than sixty blazars is most likely caused by inverse Compton scattering of soft ambient photons, the source of which is a subject of extensive debate. We investigate the influence of a dust torus on the inverse Compton emission of the relativistic electrons in the jets of Active Galactic Nuclei. This is an extension of previous studies, in which the main focus had been on target photons emitted by the accretion disk. We show that due to the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 23 publications
0
44
1
Order By: Relevance
“…Possible target photon fields are the synchrotron photons produced within the jet (the SSC process: [52,50,8]) or external photons (the EC process). Possible sources of external seed photons are accretiondisk photons entering the jet directly [22] or after being reprocessed in the circumnuclear material (e.g., the broad line regions of quasars) [77,23], jet synchrotron emission reflected off clouds in the circumnuclear material [31], infrared emission from a dust torus around the central engine [6,3]. In addition, γγ absorption, pair production, and synchrotron self absorption must be taken into account in a self-consistent leptonic blazar model.…”
Section: Leptonic Blazar Modelsmentioning
confidence: 99%
“…Possible target photon fields are the synchrotron photons produced within the jet (the SSC process: [52,50,8]) or external photons (the EC process). Possible sources of external seed photons are accretiondisk photons entering the jet directly [22] or after being reprocessed in the circumnuclear material (e.g., the broad line regions of quasars) [77,23], jet synchrotron emission reflected off clouds in the circumnuclear material [31], infrared emission from a dust torus around the central engine [6,3]. In addition, γγ absorption, pair production, and synchrotron self absorption must be taken into account in a self-consistent leptonic blazar model.…”
Section: Leptonic Blazar Modelsmentioning
confidence: 99%
“…Gamma radiation in leptonic models of broadband blazar emission is attributed to synchrotron self-Compton (Maraschi et al 1992;Bloom & Marscher 1996;Tavecchio et al 1998) or external Compton (Dermer & Schlickeiser 1993;Sikora et al 1994;Böttcher et al 1997;Dermer et al 1997;Arbeiter et al 2002) processes (see Böttcher 2002 andMadejski 2001 for recent reviews). In hadronic models, secondary photopairs and photomesons and secondary mesons are produced when energetic protons and ions interact either with ambient synchrotron photons (Mannheim & Biermann 1992;Mannheim 1993), photons of the external field (Bednarek & Protheroe 1999;Atoyan & Dermer 2000) and/or ambient matter fields .…”
Section: Introductionmentioning
confidence: 99%
“…Poutanen 2011). The second possible region for the γ-ray production is beyond the BLR (e.g., Błażejowski et al 2000;Arbeiter et al 2002;Sokolov & Marscher 2005;Yan et al 2012;Meyer et al 2015). Some multi-wavelength observations for the giant flares suggested that both the sub-millimeter and γ-rays are produced 10-20 pc from the BH (e.g., Larionov et al 2008;Sikora et al 2008), where it was assumed that γ-ray and radio emission is triggered by shocks propagating along a relativistic jet.…”
Section: Introductionmentioning
confidence: 99%